Development and Feasibility of an Adolescent Dancer Screen - Kynaston Schultz; Kathleen Sun Worrall; Zoe Tawa; Joanna Binney; Jessica Boyle; Laurel Daniels Abbruzzese (International Journal of Sports Physical Therapy)
# Background